Antibiofilm potential of Seabuckthorn silver nanoparticles (SBT@AgNPs) against Pseudomonas aeruginosa - Gondil, Vijay Singh (3 Biotech, 2019)
In era of antibiotic resistance, antibacterial silver nanoparticles are considered as potential alternative therapeutic agent to combat drug resistant pathogens. The aim of present study was to evaluate the antibacterial, antibiofilm and biocompatible potential of green synthesized Seabuckthorn silver nanoparticles (SBT@AgNPs). In the study, antibacterial efficiency of SBT@AgNPs was studied against Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli and methicillin resistant Staphylococcus aureus. SBT@AgNPs were found to possess high antibacterial activity which was indicated in terms of low minimum inhibitory and bactericidal concentrations (2–4 µg/ml) obtained against test pathogens. Anti-biofilm activity of SBT@AgNPs on young as well as mature P. aeruginosa biofilms was also evaluated. SBT@AgNPs were able to eradicate the P. aeruginosa biofilms, which was further confirmed by field emission scanning electron microscopy and confocal laser scanning microscopy. Quorum sensing assay also revealed the quorum quenching activity of SBT@AgNPs. Biocompatibility and cytocompatibility results demonstrated SBT@AgNPs to exhibit first-rate non-toxicity as no membrane damage on RBCs or detrimental morphology variation was seen in human dermal fibroblast. LC–MS analysis was also carried out to analyze the potential antibacterial chemical compounds present in aqueous extract of Seabuckthorn leaves. To the best of our knowledge this is first study in which green synthesized silver nanoparticles were exploited to eradicate young as well as mature biofilms of P. aeruginosa. Results showed that SBT@AgNPs are highly antibacterial, antibiofilm, nontoxic in nature and consequently can aid in biomedical applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13205-019-1947-6) contains supplementary material, which is available to authorized users.